Growth, Physiological, Hematological and Biochemical Responses of Growing Rabbits to Various Feeding Levels of Leucaena - Rohilla, P P; Bujarbaruah, K M; Kumar, M; Singh, G (Annals of Arid Zone, 2016)
Twenty rabbits. each of Ncw Zcaland White and Soviet Chinchilla breed.aged 12 week. were divided into four uniform groups. The first group was keptas control; in next three groups concentrate feed was substituted with 20. 40. and60% leueaena leaves (on dry matter basis). Leucaena leaves after initial rejectionwere readily consumed within one week. Highest average daily weight gain wasrecorded ] 8.88Â±1.18 g under T, and the corresponding daily OM intake was114.56Â±2.85 g. The treatment had a significant (1'